2008
DOI: 10.1055/s-2007-995741
|View full text |Cite
|
Sign up to set email alerts
|

Narrow-band imaging with magnification in Barrett’s esophagus: validation of a simplified grading system of mucosal morphology patterns against histology

Abstract: This study has validated a simplified classification of the various morphologic patterns visualized in Barrett's esophagus and confirmed its reproducibility when used by NBI-expert and non-NBI-expert endoscopists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
129
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(130 citation statements)
references
References 22 publications
0
129
0
1
Order By: Relevance
“…3 In our case on comparison of findings of magnifying endoscopy and histopathology, adenocarcinoma had irregular meandering microvessels with a partial fine network and without tubular pits ( Figure J). A demarcation line between the lesion and the surrounding mucosa clearly was revealed by magnifying endoscopy because the adjacent hyperplastic mucosa had villous pits without irregular microvessels.…”
mentioning
confidence: 55%
“…3 In our case on comparison of findings of magnifying endoscopy and histopathology, adenocarcinoma had irregular meandering microvessels with a partial fine network and without tubular pits ( Figure J). A demarcation line between the lesion and the surrounding mucosa clearly was revealed by magnifying endoscopy because the adjacent hyperplastic mucosa had villous pits without irregular microvessels.…”
mentioning
confidence: 55%
“…Singh et al [10] conducted a study on 109 patients with more than 1000 corresponding biopsies, which not only validated a simplified classification of the various morphologic patterns visualized in Barrett's Esophagus (BE) and corresponding histology with high predictive values, but also confirmed its reproducibility and repeatability when the grading system was used by both endoscopists experienced in the use of NBI and those unfamiliar with it. On the basis of the 1021 areas visualized, NBI-ME allowed correct prediction of 99% of the areas harboring intestinal metaplasia (IM) and 96% of the areas demonstrating high grade dysplasia (HGD).…”
Section: Barrett's Esophagusmentioning
confidence: 83%
“…Furthermore, ME has been confirmed as being superior to conventional colonoscopy with respect to its predictive power for diagnosing pathological neoplasms detected during endoscopy. Technological improvements in recent years have demonstrated that ME can identify the fine mucosal patterns of the gastrointestinal tract, and it is now evident that the findings obtained from this new procedure correlate positively with histological findings [19,20] , and that ME can help determine the target biopsy site during surveillance in Barrett's esophagus [5][6][7][8] .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, ME procedures for the upper gastrointestinal tract have been developed that make it possible to perform a variety of assessments, from routine observation to a detailed examination of squamous dysplasia, squamous-cell carcinoma, Barrett's esophagus and associated dysplasia/early cancer, gastric cancer, and Helicobacter pylori infection [2][3][4] . ME with a narrow band image can aid in deciding the target of endoscopic biopsy for surveillance in Barrett's esophagus [5][6][7][8] . The relationships between ME findings and gastric neoplastic histology, including the types of cancer detected, are now being investigated, and the usefulness of ME for diagnosing early gastric cancer has been reported [9][10][11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%